PENANGGULANGAN SAMPAH PLASTIK DI DESA TANGKAS KABUPATEN KLUNGKUNG DALAM PERSPEKTIF PENDIDIKAN HINDU - Ida Ayu Nindia Brahmani Putri; Ni Wayan Arini; Ni Wayan Sri Prabawati Kusuma Dewi (UHN IGB Sugriwa Denpasar, 2020)
The problem of plastic waste, lately continues to be a concern by the government of Tangkas Village, Klungkung Regency. This is because disposable plastic waste that is discarded carelessly by the surrounding community has caused disruption to the palemahan system (environment) in Tangkas Village. After five years of running its various programs, the Dharma Winangun Community Self-Help Group still exists today, although it faces several obstacles. Some of the programs are; (1) TPS-3R program (reduce, reuse, recyle); focuses on managing household-based waste that is sorted and recycled into goods with high economic value, where the program consists of short-term and medium-term, (2) Palangan-based education; in collaboration with the school to educate children from an early age, as well as the involvement of Krama Desa for the socialization of the dangers of garbage in the palemahan sistem, (3) eco tour program; environmental or ecology tourism program, which invites tourists to be involved in maintaining the preservation of Tangkas Village which consists of pray, eat and reycle activities, and finally (4) Establishment of a waste bank; the gold waste exchange program, which is held once a month, for the six related banjars that are appreciated by all villagers. Globally, the various programs above can overcome and change people's behavior to not be consumptive towards the use of plastic waste, especially those that are disposable and switch to the use of environmentally friendly products. However, in its implementation, these various programs encountered several obstacles namely, (1) internal obstacles; there are still some communities whose awareness has not yet been awakened to the danger of disposable plastic waste, limited human resources to process waste gradually, (2) external constraints; limited capacity of space and machinery in landfills (TPS), as well as in the ecotour program also face a shortage of implementation team staff. For the entire Dharma Winangun Community Self- Help Group program above, it contains Hindu Education Values, which can be summarized as follows (1) Tattwa Values education; Rta and Jnana Law, (2) Susila's educational values; awareness, sense of responsibility, application of the concept of Tri Hita Karana, Karma Phala, (3) The value of Event education; melaspas ceremonies, Tumpek Wariga, Pecaruan, and discipline to mebanten as a daily routine.